Recent trends in extractive metallurgy - Habashi F. (Journal of Mining and Metallurgy. Section B: Metallurgy)
While pyrometallurgical processes are old technology and were the dominant and logical route used to treat sulfide concentrates they are now challenged by new hydrometallurgical processes. In these new processes there have been attempts in the past few years to avoid using autoclaves in the treatment of concentrates of zinc, copper, and nickel. The situation has been recently reversed and pressure hydrometallurgy is being applied in many operations. An outline of these processes is given and the future trend is discussed.